The Statute of the International Criminal Court: A Documentary History - Bassiouni, M. Cherif (Human Rights and Humanitarian Law - Book Archive pre-2000., 1999)
The 1998 Statute of the International Criminal Court was the realization (albeit imperfect) of the oldest and longest-postponed item on the UN agenda, a judicial arm that could enforce the Universal Declaration of Human Rights and the Genocide Convention. For scholars studying this slow but crucial development in the international law of war crimes, crimes against humanity, and genocide, here is the essential documentary history: the draft statutes of 1951, 1953, 1981, and 1994, along with various related reports, the 1998 Statute, and commentary by Professor Bassiouni, who chaired the Drafting Committee of the 1998 Statute. Published under the Transnational Publishers imprint.